ANALYZING THE POSITIVE IMPACT OF VISUAL BRANDING IN IMPROVING THE PRODUCT IMAGE OF A MODERN COFFEE BUSINESS - harmiati bahar; Muh. Husriadi (Laboratorium Riset Ekonomi, 2025)
The contemporary coffee industry in Indonesia is growing rapidly among millennials and Gen Z, but MSMEs face the challenge of weak product image due to suboptimal visual branding in the era of social commerce. This study aims to analyze the positive impact of visual branding on improving the product image of contemporary coffee businesses. A qualitative method with a case study design was used, involving semi-structured interviews, observations, and thematic analysis of 10 MSMEs in Kendari City. Results show that visual elements such as earthy colors, local typography, and authentic imagery increase premium perceptions and loyalty, supported by visual ethics that prevent greenwashing. Theoretical implications enhance brand equity for emerging markets, encouraging MSMEs to implement authentic design via Instagram for coffee MSMEs.